An Empirical Investigation of the Concept of Materiality in Accounting - Frishkoff, Paul (Journal of Accounting Research, 1970)
Paul Frishkoff, An Empirical Investigation of the Concept of Materiality in Accounting, Journal of Accounting Research, Vol. 8, Empirical Research in Accounting: Selected Studies 1970 (1970), pp. 116-129